Experimental test of temperature and moisture controls on the rate of microbial decomposition of soil organic matter: preliminary results - Corey A. Palmer; Katherine P. Markstein; Lawrence H. Tanner (AIMS Geosciences, 2019)
Soil organic matter (SOM) is a major reservoir of carbon derived from the biosphere that is returned to the atmosphere largely via microbial decomposition. The potential for feedbacks between climate change and SOM decomposition makes a full understanding of the controls on SOM decomposition rates essential to modeling future climate changes. We measured soil CO2 flux in a laboratory setting using pots containing a uniform mix of soil in which we varied both temperature and moisture. Following initial desiccation, a strong CO2 pulse was measured within two hours of rewetting and a return to equilibrium conditions obtained within 168 hours, with the magnitude of the initial pulse varying by soil temperature and moisture addition. At equilibrium conditions, no correlation was found between CO2 flux and temperature across all moisture levels, although a weak positive correlation (r2=0.1 to 0.2) was seen at moderate to high moisture levels. A much stronger correlation (r2 > 0.4) was found between CO2 flux and soil moisture across the full range of temperatures and at both low and high temperatures. Thus, we conclude that when all other variables were constrained, soil moisture fluctuations appeared to have greater impact than temperature variations on the rate of microbial decomposition of SOM. These preliminary results suggest directions for future research examining the relationships between soil moisture, temperature and CO2 flux for soils in which clay mineral and/or SOM composition are varied.